Development of an enzyme-linked immunosorbent assay for detection of IgM antibodies to Babesia bigemina in cattle - Ruiz, Patrícia M Gonçalves; Passos, Lygia MF; Machado, Rosangela Z [UNESP]; Lima, José D; Ribeiro, Múcio FB (Instituto Oswaldo Cruz, Ministério da Saúde, 2001)
A crude antigenic preparation of Babesia bigemina was used to develop an ELISA for the detection of IgM antibodies. Optimal dilutions of the antigen, using positive and negative reference sera, were determined by checkerboard titrations. Negative sera from cattle imported from tick-free areas, serum samples collected from infected B. bigemina cattle were used to validate the test. The specificity was 94% and sensitivity of the Elisa 87.5%. Sera from 385 cattle deriving from areas free from tick-borne diseases, which were submitted to a preimmunization process, were screened by this technique. The Elisa detected seroconversion on the 14th day post-inoculation in animals either infested with Boophilus microplus ticks (infected with B. bigemina), or inoculated with B. bigemina infected blood. Antibody titers decreased after day 33; however, all animals remained positive until the end of the experiment (124 days). The ELISA described may prove to be an appropriate serological test for the detection of IgM antibodies against B. bigemina.
Keywords: Babesia bigemina; ELISA; IgM